Pineal Yolk Sac Tumor Producing α-Fetoprotein Detected by 68Ga-FAPI PET/MRI. (January 2022) - Dai, Yaqing; Pang, Yizhen; Bao, Weiqi; Cheng, Yuanyuan; Chen, Haojun
Abstract : Abstract: Pineal yolk sac tumors (YSTs) are a rare type of extragonadal YST. They make up a small fraction of all intracranial germ cell tumors and an even small fraction of pineal masses overall. This study reported a case of pineal YST with α-fetoprotein production revealed by 18 F-FDG and 68 Ga-FAPI PET/MRI. In the PET images, 68 Ga-FAPI showed a far better tumor-to-background ratio than 18 F-FDG in the pineal YST because there is little 68 Ga-FAPI uptake in the brain. This case indicates that 68 Ga-FAPI PET/MRI may be a useful tool for evaluating intracranial YST and other types of tumors in central nervous system.